On the distribution of the number of phases per possession in 2025 Men's Six Nations rugby - Burdick, B. A. (Journal of Sports Analytics, 2026)
Data from the Men's 2025 Six Nations are analyzed to determine the number of possessions in a match and the distribution of the number phases per possession in international rugby. Each team can expect an average of 50 possessions in a match. The distribution is approximately geometric with the expected probability of possession being lost in any given phase of 0.365. Systematic deviations from the geometric distribution, however, showed phases in which the observed number of possession endings exceeded the expected counts. The discrete Weibull distribution reduced the number of deviations in which the observed number of counts exceeded the expected number. We conclude that the discrete Weibull distribution is more congruent with the distribution of the number of phases per possession. Under the discrete Weibull distribution, the value of expected probability can change (in this case, to decrease) methodically as the phases increase. This effect on the phases per possession is, we believe, a novel observation not previously described in the rugby literature. It is likely that the overall distribution results from the constraints imposed by of the Laws of the Game, Referee's interpretations, and, importantly, common overall coaching approaches to playing the game.